Evaluating the Staffing of an Interlibrary Loan Unit: An Exercise in Data-Driven Decision Making and Debunking "Anecdata" - Harris, Colleen S. (Journal of access services, 2014)
The former Head of Access Services of the University of Tennessee at Chattanooga Library reports on the recent attempt to restructure the interlibrary loan unit of the department. Reviewing workflows, data reports, technology use, and staff assignments precipitated staffing changes that allowed the Library to become more efficient and to reallocate librarian time to library areas in need of greater support due to changing workflows across the organization. The greatest challenges proved to be moving beyond unfounded perception (or "anecdata") when making decisions, determining staff members' skill strengths and weaknesses, and changing established work habits. Short-term benefits included improved workflows, improved ability to handle absences and student worker scheduling, and reduced staff stress.